Assessment of the level of knowledge of colorectal cancer among public at outpatient clinics in Serdang Hospital: a survey based study - Yan, Pan; Chieng, Jin Yu; Haris, Ahmad Amirul Hafiz; Ang, Shih Yuan (Malaysia Medical Association, 2017)
Objectives: Colorectal cancer (CRC) is one of the most common gastrointestinal cancers in the world. In the Asia- Pacific region, it is the fastest emerging gastrointestinal cancer. Level of awareness on CRC warning signs and risk factors in the rural population of Malaysia is reported of very low. The aim of this study was to assess the level of knowledge of CRC among the public at medical outpatient clinics in Serdang Hospital. The association between sociodemographic factors with level of knowledge among the respondents was further studied. Study design: A study was conducted among the non-CRC patients' relatives accompanying their relatives to the medical outpatient clinics in Serdang Hospital from 1st April to 31st August 2016. The study was carried out with cluster sampling method. Methods: The respondents were assessed using validated and modified Cancer Awareness Measures (CAM) questionnaire consists of three parts which are knowledge on warning signs, knowledge on risk factors and sociodemographic factors. All data were analysed using IBM SPSS Statistics 21.0. Results: Altogether 308 subjects completed the questionnaires. It was shown high percentage of good knowledge for warning signs and risk factors of CRC among the respondents. A significant association between age groups and level of income with level of knowledge on warning signs was observed. Conclusions: The level of knowledge of CRC among the general public in Serdang Hospital was sufficient. The respondents with higher income or younger age had higher level of knowledge regarding CRC.